اثر غياب جهاز العلاقات العامة على الاداء الوظيفي للمؤسسات الجزائرية - حنان سراي; وصال مرزوق (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة: تهدف مشكلة الدراسة في تأثير غياب جهاز العلاقات العامة على الأداء الوظيفي داخل المؤسسات الجزائرية "مؤسسة اتصالات الجزائر بالأغواط". والأسباب التي دفعت بنا لاختيار هذا الموضوع هي الإحساس بأهمية الموضوع وكذا الرغبة في المساهمة في تطوير العلاقات العامة في المؤسسات الجزائرية : من خلال تسليط الضوء على أهميتها وأدوارها المختلفة وتحديد الحدبات التي تواجهها واقتراح حلول مناسبة لها,وكذلك غياب الاهتمام بالعلاقات العامة في المؤسسات الجزائرية :حيث لا يتم تخصيص مصلحة مستقلة لها في كثير من المؤسسات مما قد تأثر سلبا على أدائها. واعتمدنا في دراستنا لبلوغ الأهداف المرجوة على مجموعة من التساؤلات تتمثل في التساؤل الرئيسي وهو كيف تؤثر غياب مصلحة العلاقات العامة على الأداء الوظيفي للمؤسسات الجزائرية؟. وتساؤلات فرعية كالآتي : 1. ما لهي العوامل الرئيسية التي تساهم في تحسين مصلحة العلاقات العامة وتعزيز الأداء الوظيفي في الشركات الجزائرية؟ 2. هل إستخدام وسائل الاعلامله تأثير سلبي على الأداء الوظيفي في ظل غياب مصلحة العلاقات العامة ؟ ومن أجل الإجابة على إشكالية بحثنا اعتمدنا على المنهج "الوصفي التحليلي "وهذا لكونه الأكثر ملائمة لموضوع الدراسة ,واعتمدنا على المقابلة كأداة لجمع البيانات . وقد قمنا باختيار مجتمع بحثنا في هذه الدراسة بناءا على إبراز طبيعة المجتمع في حد ذاته والمتمثل في كل من رئيس مصلحة الممتلكات والتأمينات السيد بوخلخال علي , الذي قام رئيس المؤسسة بتوجيهنا إليه من أجل الخبرة التي لديه,والسيد المكلف بالإعلام .وتمثلت خطة بحثا في أربعة فصول بحيث الفصل الأول يأخذ الإطار المنهجي والإطار النظري يظم فصلين بحيث فصل يوحي إلى ماهية العلاقات العامة وفصل إلى عموميات الأداء الوظيفي والفصل الرابع عن الإطار الميداني للدراسة حاولنا من خلاله الوقوف على الإجابة للإشكالية التي طرحناها في الأول ووصلنا إلى نتائج بعد جمع معلومات ومناقشتها وبعد تناولنه من أطرافه المتعددة وجوانبه المختلفة وصلت إلى أهم النتائج وهي : 1. لايوجد أثر غياب مصلحة العلاقات العامة داخل مؤسسة اتصالات الجزائر لأن كل واحد لديه مهامه الخاص الذي يقوم به 2. عندما يكون هناك تواصل واتصال فعال تكون هناك حلقة تفاهم بين المؤسسة جمهورها الداخلي والخارجي 3. اتضح لنا أنه يوجد علاقات عامة في المؤسسات الجزائرية إلى أنها كل مؤسسة تختلف بتسميتها ولكن يقتصر عملها على العلاقات الخارجية للمؤسسات أي الجمهور الداخلي 4. تبين لنا أن الموظفين يدركون كيف يقومون بتحسين أدائهم ويسعونا إليها Abstract : The problem of the study was the impact of the absence of an official public relations department on job performance within Algerian institutions, the Algerian Telecom Corporation in Laghouat, and the reasons that prompted us to choose this topic were the sense of the importance of the topic, as well as the desire to contribute to the development of public relations in Algerian institutions by highlighting its importance and its various roles. Identifying the pitfalls they face and proposing appropriate solutions for them, as well as the lack of interest in public relations in Algerian institutions, as no independent department is allocated to them in many institutions, which may negatively affect their performance. We relied in our study to achieve the desired goals on a set of questions represented by the main question, which is how does it affect The absence of the public relations interest on the functional performance of Algerian institutions and the sub-questions are as follows: 1. What are the main factors that contribute to improving the interest of public relations and strengthening Job performance in the context of Algerian companies?. 2. Does the use of the media have a negative impace on career performance in the absence of public relations? In order to answer the problem of our research, we relied on the descriptive analytical approach, and this is because it is the most appropriate to the subject of the study. We relied on the interview as a tool for all the data. We chose the community we researched in this study based on highlighting the nature of the community in itself, which is represented by each of the presidents. The Department of Property and Insurance, Mr. Ali BouKhalkal, whom the head of the institution directed us to for the sake of the experience he has, and the master in charge of information, and the plan of two research papers was represented in four chapters, so that the first chapter takes the methodological framework and the theoretical framework includes two chapters, so that a chapter suggests the nature of public relations, a chapter on the generalities of job performance, and the fourth chapter. Regarding the field framework of the study, we tried through it to find the answer to the problem that we raised in the first place, and we arrived at results after collecting and discussing the information, and after it was discussed by the speakers and a different answer. We arrived at the most important results, which is one. There is no trace of the absence of the public relations department within the Algeria Telecom Corporation, because each one has one. Its special tasks are carried out by two people. When there is communication and effective communication, there is a link of understanding between the institution and its internal and external audiences. It turns out that there are public relations in Algerian institutions that each institution is different in its name, but its work is limited to the external relations of the institutions, the external audience of the institution. Turns out the staff are aware of how to improve their performance and seek it. I want to translate it
دراسة ميدانية بمؤسسة اتصالات اتلاجزائر بالاغواط انموذجا